MADHUBANI FOLK PAINTINGS AND AMAZING COMBINATION OF COLORS: मधुबनी लोक चित्रकला की विशेषताएॅं एवं रंगों का अदभुत संयोजन - Kumar, Lal Bahadur (International Journal of Research -GRANTHAALAYAH, 2014)
Through the Madhubani Lak Chitrakala of Mithilanchal, the tradition of Lakkitra is still being maintained. The art of the art is dynamic even today, based on the Sh वंशi dynasty tradition. Madhubani paintings are in great demand abroad but they are neglected in their own country. It is unfortunate that those who have skills in their hands are poor on the rural artist. The country's art world did not get noticed, while "Hasebhawa of Japan has established the Mithila Museum on a hill in Niigata, northwest of the capital Takia." "Hasegawa", a Japanese art admirer and art connoisseur, has visited India more than twenty five times. He also went to the residence of many famous artists of Madhubani paintings and discussed the combination of techniques and colors with the artists of Mithila and Madhubani paintings. After understanding, Mithila artists went to Japan with them and also painted them. Apart from this, many artists visiting America, England, South Africa, France, Germany, Mauritius have made people aware of this art and have raised the value of the country. मिथिलांचल की मधुबनी ल¨क चित्र्ाकला के माध्यम से ल¨कचित्र्ा परम्परा का निर्वाह आज भी किया जा रहा है। यहाँ की ल¨क कला श्©ली वंश परम्परा के आधार पर आज भी गतिशील है। मधुबनी ल¨क चित्र्ाकला की विदेश¨ं में काफी मांग है ल्¨किन वह अपने ही देश में उपेक्षित है। दुर्भाग्य की बात है कि जिनके हाथ में हुनर है, वे ग्रामीण कलाकार आमत©र पर गरीब हैं। देश के कला-जगत् की नजर इस पर नहीं गई, जबकि ‘‘जापान के हासेभावा ने राजधानी ट¨किय¨ से उत्तर-पश्चिम में स्थित निगाता में एक पहाड़ी पर मिथिला म्यूजियम की स्थापना की है। जापान के कला के मर्मज्ञ एवं कला पारखी ‘‘हासेगावा’’ पच्चीस से अधिक बार भारत आ चुके हैं। वे मधुबनी ल¨क चित्र्ाकला के कई सुप्रसिद्ध कलाकार¨ं के आवास पर भी गए अ©र मिथिला के कलाकार¨ं से मधुबनी ल¨क चित्र्ाकला के माध्यम व तकनीक एवं रंग¨ं के संय¨जन पर चर्चा की अ©र उनक¨ समझने के बाद मिथिला कलाकार¨ं क¨ अपने साथ जापान ल्¨ जाकर चित्र्ा रचना भी कराई। इसके अलावा अमेरिका, इंग्ल्©ण्ड, दक्षिण अफ्रीका, फ्रांस, जर्मनी, मॉरीशस जाकर कई कलाकार¨ं ने इस ल¨क कला श्©ली से ल¨ग¨ं क¨ अवगत कराया अ©र देश का मान बढ़ाया है।